Application of the Health Belief Model to Compliance with the Use of Personal Protective Equipment by Laundry Staff: A Systematic Literature Review - Maulana, Irvan; Winarti, Eko; Mohamad, Norfidah (Journal of Health Sciences, 2024)
Personal protective equipment is essential to safeguard workers from potential hazards in the workplace, including chemicals, dust, heat, or germs. The proper use of personal protective equipment can prevent or reduce injuries and illnesses at work. The goal of this literature review is to explore research on the utilization of personal protective equipment by hospital laundry workers based on the health belief model. The systematic literature review is the chosen method for conducting this study. It is a scientific approach employed to analyze, assess, synthesize, and critique research findings on specific themes or issues. To enhance compliance with personal protective equipment among laundry personnel, it is crucial to elevate knowledge and awareness, address unfavorable attitudes or perceptions, provide resources and comfort, implement adequate supervision and procedures, and foster a supportive organizational culture. Healthcare organizations can promote adherence to personal protective equipment guidelines among laundry staff by offering instruction and training, facilitating communication and awareness, providing administrative support, enforcing oversight, setting positive role models, continuously evaluating, and improving procedures, engaging employees, and ensuring ongoing support and resources.